All‐Inorganic CsPbBr3 Perovskite Nanocrystals/2D Non‐Layered Cadmium Sulfide Selenide for High‐Performance Photodetectors by Energy Band Alignment Engineering. (20th July 2021) - Peng, Mingfa; Ma, Yulong; Zhang, Lei; Cong, Shan; Hong, Xuekun; Gu, Yiheng; Kuang, Yawei; Liu, Yushen; Wen, Zhen; Sun, Xuhui
Abstract: Perovskites have attracted intensive attention as promising materials for the application in various optoelectronic devices due to their large light absorption coefficient, high carrier mobility, and long charge carrier diffusion length. However, the performance of the pure perovskite nanocrystals‐based device is extremely restricted by the limited charge transport capability due to the existence of a large number of the grain boundary between perovskite nanocrystals. To address these issues, a high‐performance photodetector based on all‐inorganic CsPbBr3 perovskite nanocrystals/2D non‐layered cadmium sulfide selenide heterostructure has been demonstrated through energy band engineering with designed typed‐II heterostructure. The photodetector exhibits an ultra‐high light‐to‐dark current ratio of 1.36 × 10 5, a high responsivity of 2.89 × 10 2 A W −1, a large detectivity of 1.28 × 10 14 Jones, and the response/recovery time of 0.53s/0.62 s. The enhancement of the optoelectronic performance of the heterostructure photodetector is mainly attributed to the efficient charge carrier transfer ability between the all‐inorganic CsPbBr3 perovskites and 2D cadmium sulfide selenide resulting from energy band alignment engineering. The charge carriers' transfer dynamics and the mechanism of the CsPbBr3 perovskites/2D non‐layered nanosheets interfaces have also been studied by state‐state PL spectra, fluorescence lifetime imaging microscopy, time‐resolved photoluminescence spectroscopy, and Kelvin probe force microscopy measurements. Abstract : A high‐performance photodetector based on an all‐inorganic CsPbBr3 perovskite nanocrystals/2D non‐layered cadmium sulfide selenide heterostructure is demonstrated through energy band engineering with designed typed‐II heterostructure. Compared with pure CsPbBr3 NCs and 2D‐non‐layered cadmium sulfide selenide devices, the responsivity of the heterostructure photodetector is enhanced by 406 times and 59 times, and the detectivity is improved over 700% and 1100%, respectively.